Revisiting Investor Behaviour in Risky Investment Decision Making - Darmayanti, Ni Putu Ayu; Wiagustini, Ni Luh Putu; Sri Artini, Luh Gede; Rika Candraningrat, Ica (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
The number of studies into behavioral finance has increased during the last two decades. However, literature about how behavioral factors determine risky investment decisions still needs to be reviewed from the behavioral finance theory point of view. This paper deals with behavioral research in finance and some aspects of investor behavior when making investment decisions about risky assets. Library research was conducted and then presented using a descriptive form of theoretical exposure. Based on the perspectives of the prospect theory, the literature reviewed in this paper provides results about individuals' financial literation, risk tolerance, and personality in determining motivation to choose risky investments. The conclusions show that behavioral finance exists, and people may be irrational when making investment decisions about risky assets.